Respuesta :
Answer:Answer:
d=√
−2x2+y
900f4i2n2x
or d=−√
−2x2+y
900f4i2n
Step-by-step explanation:
Let's solve for d.
y=2x2+9xfindf(10)findf(10)
Step 1: Flip the equation.
900d2f4i2n2x+2x2=y
Step 2: Add -2x^2 to both sides.
900d2f4i2n2x+2x2+−2x2=y+−2x2
900d2f4i2n2x=−2x2+y
Step 3: Divide both sides by 900f^4i^2n^2x.
900d2f4i2n2x
900f4i2n2x
=
−2x2+y
900f4i2n2x
d2=
−2x2+y
900f4i2n2x
Step 4: Take square root.
d=√
−2x2+y
900f4i2n2x
or d=−√
−2x2+y
900f4i2n2x
2x
Answer:
d=√
−2x2+y
900f4i2n2x
or d=−√
−2x2+y
900f4i2n
Answer:Answer:
d=√
−2x2+y
900f4i2n2x
or d=−√
−2x2+y
900f4i2n
Step-by-step explanation:
Let's solve for d.
y=2x2+9xfindf(10)findf(10)
Step 1: Flip the equation.
900d2f4i2n2x+2x2=y
Step 2: Add -2x^2 to both sides.
900d2f4i2n2x+2x2+−2x2=y+−2x2
900d2f4i2n2x=−2x2+y
Step 3: Divide both sides by 900f^4i^2n^2x.
900d2f4i2n2x
900f4i2n2x
=
−2x2+y
900f4i2n2x
d2=
−2x2+y
900f4i2n2x
Step 4: Take square root.
d=√
−2x2+y
900f4i2n2x
or d=−√
−2x2+y
900f4i2n2x
2x
Answer:
d=√
−2x2+y
900f4i2n2x
or d=−√
−2x2+y
900f4i2n